A cyclic catalysis enhanced electrochemiluminescence aptasensor based 3D graphene/photocatalysts Cu2O-MWCNTs. (20th August 2018) - Wu, Yeyu; Li, Xiaoyu; Tan, Xuecai; Feng, Defen; Yan, Jun; Zhang, Hui; Chen, Xiao; Huang, Zaiyin; Han, Heyou
Abstract: Here, we developed an electrochemiluminescence (ECL) aptasensor for ultrasensitive detection of thrombin (TB) based on a synergistic effect of nanoparticles sensitization and cyclic catalysis of Cu2 O. The aptasensor is constructed from three parts: firstly, three dimensional (3D) graphene was dropped onto the electrode to accelerate electron transfer. Then, the synthesized Cu2 O-multiwalled carbon nanotubes (MWCNTs) were loaded onto the surface of 3D graphene. Finally, after TB aptamers linked to MWCNTs, Ru(bpy)3 2+ - doped silica nanoparticles (RuSiNPs) were marked onto the surface. When detection of TB, the aptamers folded into G-quadruplex's that made the RuSiNPs get closer to the Cu2 O. As a photocatalysis, Cu2 O was excited by the ECL of RuSiNPs and generated holes and electrons which could catalyze the ECL reaction to emit much light, and the light could excite Cu2 O again. Hence, a cyclic catalytic aptasensor was built. Under the optimal conditions, this aptasensor for TB detection showed good sensitivity with wide linearity (5 × 10 −15  M - 5 × 10 −11  M) and low detection limit (1.3 × 10 −15  M). Highlights: Use photocatalysts property of Cu2 O to build a cyclic catalysis amplified ECL aptasensor. Use the synergy of 3D graphene and MWCNTs to further enhance the ECL signal. The developed aptasensor exhibited low detection limit and wide linear range for thrombin detection.